A gridded inventory of anthropogenic methane emissions from Mexico based on Mexico's national inventory of greenhouse gases and compounds. (8th October 2020) - Scarpelli, Tia R; Jacob, Daniel J; Octaviano Villasana, Claudia A; Ramírez Hernández, Irma F; Cárdenas Moreno, Paulina R; Cortés Alfaro, Eunice A; García García, Miguel Á; Zavala-Araiza, Daniel
Abstract: We present a gridded inventory of Mexico's anthropogenic methane emissions for 2015 with 0.1° × 0.1° resolution (≍10 × 10 km 2 ) and detailed sectoral breakdown. The inventory is constructed by spatially allocating national emission estimates from the National Inventory of Greenhouse Gases and Compounds constructed by the Instituto Nacional de Ecología y Cambio Climático (INECC). We provide additional breakdown for oil/gas emissions. Spatial allocation is done using an ensemble of national datasets for methane-emitting activities resolving individual municipalities and point sources. We find that emissions are highest in central Mexico and along the east coast, with substantial spatial overlap between major emission sectors (livestock, fugitive emissions from fuels, solid waste, and wastewater). Offshore oil/gas activities, primarily oil production, account for 51% of national oil/gas emissions. We identify 16 hotspots on the 0.1° × 0.1° grid with individual emissions higher than 20 Gg a −1 (2.3 tons h −1 ) including large landfills, offshore oil production, coal mines in northern Mexico, a gas processing complex, and a cattle processing facility. We find large differences between our inventory and previous gridded emission inventories for Mexico, in particular EDGAR v5, reflecting our use of more detailed geospatial databases. Although uncertainties in methane emissions remain large, the spatially explicit emissions presented here can provide the basis for inversions of atmospheric methane observations to guide improvements in the national inventory. Gridded inventory files are openly available at (https://doi.org/10.7910/DVN/5FUTWM ).